Implementation of Corporate Social Responsibility (CSR) On Islamic Banking: Maqasid Sy ariah’ s Approach - Nurizal Ismail; Ahmad Muqorobin (Islamic Economics Journal, 2017)
Islamic banking as corporate is also subjected to the responsible of Corporate social responsibility (CSR). Moreover, Islamic Banking is different from Conventional bank in its worldview, operation and principle. It will impact to CSR operation in Islamic banking. CSR of Islamic Banking must constitute to its objective that should realize the just and welfare in ummah’s life. It came into existence as a collective religious obligation (fard kifayah) on the larger community (Ummah) as a financial intermediary for individuals in the community wishing to comply with Islamic law (Syari’ah). This study aims to discuss the role of maqasid Syari’ah, and to propose it into the applied of CSR on Islamic banking. Implementation of corporate social responsibility (CSR) is very important in Islamic banks because it is used as importantmeasurements to assess a successful company in its operation. CSR in Islamic bank should be different with the Conventional one from its worldview, system and standard of operational. The concept of CSR in Islam is not new, it is deeply mentioned and explained in sources of Islam. Maqasid Syari’ah is used to see the maslahat (benefit) and to make decision in all aspect of human life. In maslahat’s perspective, CSR of Islamic bank is to promote the justice and welfare and to avoid the disruption and chaos.